Detrital zircon U–Pb ages of the Proterozoic metaclastic-sedimentary rocks in Hainan Province of South China: New constraints on the depositional time, source area, and tectonic setting of the Shilu Fe–Co–Cu ore district. (1st December 2015) - Wang, Zhilin; Xu, Deru; Hu, Guocheng; Yu, Liangliang; Wu, Chuanjun; Zhang, Zhaochong; Cai, Jianxin; Shan, Qiang; Hou, Maozhou; Chen, Huayong
Highlights: Shihuiding Formation is re-interpreted as the top, Seventh member of the Shilu Group. Shilu Group and interbedded BIFs have a maximum depositional time of 1070–970 Ma. A marine, retroarc foreland basin proposed for the host rocks and interbedded BIFs. Precursors to the Shilu Group were dominantly derived from Laurentia. Hainan Island was most likely attached or close to northwestern Laurentia in Rodinia. Abstract: The Shilu Fe–Co–Cu ore district, located at Hainan Province of South China, is well known for high-grade hematite-rich Fe ores and also two Precambrian host successions, i.e. the Shilu Group and the overlying Shihuiding Formation. This district has been interpreted as a banded iron formation (BIF) deposit-type, but its depositional time, source area and depositional setting have been in debate due to poor geochronological work. Detrital zircon U–Pb dating aided by cathodoluminescence imaging has been carried out on both the Shilu Group and Shihuiding Formation. Most of the zircon grains from both the successions are subrounded to rounded in morphology and have age spectra between 2000 Ma and 900 Ma with two predominant peaks at ca. 1460–1340 Ma and 1070 Ma, and three subordinate peaks at ca. 1740–1660 Ma, 1220 Ma and 970 Ma. The similar age distribution suggests the same depositional system for both successions. Linked to the geological and paleontological signatures, the Shihuiding Formation is better re-interpreted as the top, i.e. Seventh member of the Shilu Group, rather than a distinct Formation. The youngest statistical zircon age peaks for both successions, i.e. ca. 1070–970 Ma may define the maximum depositional time of the Shilu Group and interbedded BIFs. At least two erosional sources are required for deposition of the studied detrital zircons, with one proximal to provide the least abraded zircons and the other distal or recycled to offer the largely abraded zircons. The predominance of rounded or subrounded zircons over angular zircons probably implies a relatively stable tectonic setting during deposition. Given the Precambrian tectonics of Hainan Island, a retro-arc foreland basin is proposed for the deposition of the Shilu Group and interbedded BIFs. In comparison with those from the South China and other typical Grenvillian orogens, the detrital zircon age populations reveal that Hainan Island had crystalline basement similar to neither the Yangtze nor the Cathaysia Blocks. Combined with the tectonothermal events, we propose that Hainan Island was independent of South China at least before the late Ordovician and most likely attached or close to northwestern Laurentia before the breakup of Rodinia.